International Patterns of Teacher Discontent - Scott, Catherine; Stone, Barbara; Dinham, Steve (Education Policy Analysis Archives, 2001)
This article reports the results of research into the career motivation and satisfaction of a sample of over 3,000 teachers and school administrators in four countries: Australia, New Zealand, England, and the USA. Using the participants' own words, we explore the effects on educators of recent international educational change, understood here as a subcategory of more general social trends. Bourdieu's concepts of the Right and Left Hands of the state are used to interpret the experience of teaching in a climate where, while more is expected and demanded of schools, and schools and teachers are scrutinised as never before, educational resources have become scarcer, and the status and image of teaching as a profession has declined.